Field load tests on a Queen-post timber truss - Branco, J. (2012)
In-situ cyclic tests on a Portuguese Queen-post timber truss were performed. The main goal of the tests was to evaluate the overall behaviour of the timber truss under symmetric and nonsymmetric loading. Moreover, the influence of the number and location of point loads, without and with eccentricity relatively to joints, was assessed. The carrying tests were preceded by a visual inspection and non-destructive evaluation aiming to collect geometric data and to assess the decay level presented by the timber elements. The tests results have been reproduce through a finite element model assuming the moment-rotation laws proposed in previous research steps for the joints behaviour.